Preliminary data on the activity of male and female common pheasants Phasianus colchicus during the breeding period in a Mediterranean area (Avocetta, 2024)
Assessing patterns of activity rhythms in wildlife is pivotal for species conservation. In this work, we aimed at determining the curve of activity rhythms of male and female common pheasants Phasianus colchicus in a Mediterranean area in central Italy. We used camera-trapping and we computed the inter-sexual temporal overlap of activity rhythms in the breeding period. We collected 129 independent records of common pheasants (males, N = 90; females, N = 39). Males were mostly active in the morning, whereas female activity was mostly concentrated at dawn and dusk, showing an intermediate overlap of diurnal activity rhythms (Δ1 = 0.55).  Recorded patterns of activity rhythms confirmed the importance of ecotones for the conservation of this species, which represent an important prey for several native carnivores.